((w-1)+w)*((w-2)+3w)=0

Simple and best practice solution for ((w-1)+w)*((w-2)+3w)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((w-1)+w)*((w-2)+3w)=0 equation:


Simplifying
((w + -1) + w)((w + -2) + 3w) = 0

Reorder the terms:
((-1 + w) + w)((w + -2) + 3w) = 0

Remove parenthesis around (-1 + w)
(-1 + w + w)((w + -2) + 3w) = 0

Combine like terms: w + w = 2w
(-1 + 2w)((w + -2) + 3w) = 0

Reorder the terms:
(-1 + 2w)((-2 + w) + 3w) = 0

Remove parenthesis around (-2 + w)
(-1 + 2w)(-2 + w + 3w) = 0

Combine like terms: w + 3w = 4w
(-1 + 2w)(-2 + 4w) = 0

Multiply (-1 + 2w) * (-2 + 4w)
(-1(-2 + 4w) + 2w * (-2 + 4w)) = 0
((-2 * -1 + 4w * -1) + 2w * (-2 + 4w)) = 0
((2 + -4w) + 2w * (-2 + 4w)) = 0
(2 + -4w + (-2 * 2w + 4w * 2w)) = 0
(2 + -4w + (-4w + 8w2)) = 0

Combine like terms: -4w + -4w = -8w
(2 + -8w + 8w2) = 0

Solving
2 + -8w + 8w2 = 0

Solving for variable 'w'.

Factor out the Greatest Common Factor (GCF), '2'.
2(1 + -4w + 4w2) = 0

Factor a trinomial.
2((1 + -2w)(1 + -2w)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(1 + -2w)' equal to zero and attempt to solve: Simplifying 1 + -2w = 0 Solving 1 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2w = 0 + -1 -2w = 0 + -1 Combine like terms: 0 + -1 = -1 -2w = -1 Divide each side by '-2'. w = 0.5 Simplifying w = 0.5

Subproblem 2

Set the factor '(1 + -2w)' equal to zero and attempt to solve: Simplifying 1 + -2w = 0 Solving 1 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2w = 0 + -1 -2w = 0 + -1 Combine like terms: 0 + -1 = -1 -2w = -1 Divide each side by '-2'. w = 0.5 Simplifying w = 0.5

Solution

w = {0.5, 0.5}

See similar equations:

| X^3-10x^2+12x+72=0 | | 9x-3=5x | | 2c-3(c-5)=4(2c+1)-3c | | 3m^2=6m | | A=1-2(.050)-.020 | | -4(12y)= | | A=1-2(.05)-20 | | -5-12=8x+16-7x | | z^2+4z=21+z-3 | | 4(k-4)-8(k+4)=5(3k-4)-9(3k+4) | | A=1-2(50)-20 | | 3x^2+6x+5x^2-20y-13=0 | | 4b-4-7b-6= | | (2x-1)(2x^3-50x)=0 | | 8x^2-5x=9 | | -1+5=m-7 | | x(3+5)2= | | 2m^2=m^2+36 | | 41y=8(5y-6) | | 12x^2=36 | | y^2-2y-8=0 | | x^2-63=9x | | 8x^2=-5x-9 | | -3(7d+6)= | | X^2+2x+y^2+14y-31=0 | | 7-(3y-4)= | | 2x-8x+6x-3x= | | 5m=12m-30 | | x^2-0.1x-0.02=0 | | 3(3x-2)=10x | | 16x^2-96x-9y^2+36y-36=0 | | 6x^2+4x-2=0 |

Equations solver categories